Optimization of Irrigation and Fertilization in Maize–Soybean System Based on Coupled Water–Carbon–Nitrogen Interactions - Aizheng Yang; Shuyuan Luo; Yaowen Xu; Pingan Zhang; Zhenyi Sun; Kun Hu; Mo Li (Agronomy)
Effective water and nitrogen management plays a pivotal role in enhancing crop yields while simultaneously reducing greenhouse gas emissions. This study differs from previous research by investigating the effects of water–nitrogen co-regulation involving organic carbon on the yield increase and emission mitigation in a soybean–maize system. A dryland experiment was conducted, employing 20 distinct combinations of water and nitrogen treatments that were meticulously designed for the maize–soybean system. The DSSAT crop model was employed to quantitatively elucidate the intricate interactions between water and nitrogen. A multi-objective optimization model, integrating experimental data and mechanistic insights, was constructed and refined using the NSGA-III genetic algorithm to identify the optimal water and nitrogen application ratios. An analysis of maize and soybean data from Acheng in Heilongjiang, China, indicates that optimized irrigation and nitrogen application regimes—152.2 mm and 247.1 kg·ha−1 for maize and 91.7 mm and 106.2 kg·ha−1 for soybean—substantially enhanced the net economic returns within the dryland ecosystem. There is a significant positive correlation between the yield (Y), soil nitrogen content, and soil organic carbon (SOC). Nitrate nitrogen has a significant positive correlation with CO2 gas emissions. Organic carbon changes the soil’s carbon to nitrogen ratio by participating in the water and nitrogen cycles, thereby affecting nitrogen and phosphorus loss and carbon emissions. This study presents a sustainable method for regulating water and nitrogen in the maize–soybean system.